Do Service Learning and Active-Citizenship Learning Support Our Students to Live a Culture of Democracy? - Geier, Ingrid; Hasager, Ulla (Frontiers in Education, 2020)
Civic thinking and civic attitude require values and norms for social togetherness and social engagement. Service learning and active-citizenship learning are high-impact pedagogies, well documented as supporting civic-mindedness and a culture of democracy sustainably. Though our study is part of a broader research project, this brief research report already documents the impact of the two pedagogies on civic-mindedness and students’ democratic awareness. Through a mixed-method design we implemented a quantitative survey (7 level Likert Scale) of undergraduate student learning outcomes of service learning with 55 students from the University of Hawaiʻi at Mānoa and 41 students practicing active-citizenship learning at Salzburg University of Teacher Education. We found that the two pedagogies significantly support students' democratic awareness and civic attitudes. In addition to the survey, a qualitative analysis is in progress based on 23 focus group discussions, conducted to detail how the students experience themselves when they take on social responsibility, e.g. when they actively participate in improving their society. Our mixed, but narrowly focused, approach combined with well-established measuring tools and scales is a first study of how to assess Attitudes, one of the four fundamental principles of the Council of Europeʻs Competency Model for a Democratic Culture.